2015
DOI: 10.1039/c5ta00292c
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced hydrogen storage properties of a Mg–Ag alloy with solid dissolution of indium: a comparative study

Abstract: A comparative study of Mg 5.7 In 0.3 Ag and Mg 6 Ag alloys was conducted to reveal the effects of indium (In) solid solutions on the hydrogen storage properties of Mg-based alloys. Different from the Mg 6 Ag alloy, the as-cast Mg 5.7 In 0.3 Ag alloy was composed of a Mg(In) solid solution and Mg 3 Ag. However, an initial hydrogen absorption/desorption treatment (i.e., activation) propelled the In atoms in Mg(In) toward Mg 3 Ag, forming (Mg, In) 3 Ag in the activated sample. This transformation involving the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…This is confirmed by hydrogen sorption kinetics studies of Alloy 8, Alloy 9, and Alloy 10 (AgMg, Ag60Mg40, and Ag 3 Mg) samples, which do not absorb hydrogen, and structural analysis performed after hydrogen sorption measurements. Similar observations have also been reported previously [ 14 , 15 , 19 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This is confirmed by hydrogen sorption kinetics studies of Alloy 8, Alloy 9, and Alloy 10 (AgMg, Ag60Mg40, and Ag 3 Mg) samples, which do not absorb hydrogen, and structural analysis performed after hydrogen sorption measurements. Similar observations have also been reported previously [ 14 , 15 , 19 ].…”
Section: Resultssupporting
confidence: 93%
“…Alternatively, these low values might be related to the presence of an insignificant amount of residual magnesium or hydrogen absorbing phase. The thermodynamic discussion and reaction mechanisms for Mg-Ag phases with hydrogen have already been shown in the literature [ 14 , 15 , 18 , 19 ], and for that reason, they will no longer be explored in this paper. We discuss only the kinetics of the absorption and the properties of the manufactured material.…”
Section: Resultsmentioning
confidence: 99%
“…Improvement in sorption characteristics was recently confirmed in In-containing alloys Mg-Ag [35], Mg-In-Ni [36] as well, and in an experimental survey [14].…”
Section: Introductionmentioning
confidence: 86%
“…Later, the groups of Luo and Lu reported that alloying with Y and Ni to form solid solutions of Mg−In−Y and Mg−In−Ni, respectively, could further destabilize the thermodynamics of Mg‐based alloys. In addition to the Mg−In solid solution alloy systems, the Mg−Cd, Mg−Si, and Mg−Ag systems also show improved hydrogen‐storage kinetics and thermodynamics compared with those of pure Mg−MgH 2 .…”
Section: Approaches For Hydrogen‐storage Performance Enhancementmentioning
confidence: 99%